As práticas curriculares de professores(as): olhares para as experiências culturais negras e saberes quilombolas em Santa Luzia do Norte e a produção artística de mestre José Zumba - Silva, Beatriz Araújo da (2017)
This master's thesis, developed in the Post-Graduation Program of the Education Center of the Federal University of Alagoas, addresses a study on the curricular practices of teachers and their view on black and quilombola cultural knowledge in Santa Luzia do Norte‟s county and their relation with paintings of Mestre José Zumba (SILVA, 2014). We seek to investigate the extent to which curriculum practices of teachers at a quilombola school experience their knowledge and their black cultural practices, including the recognition of the artist's production referenced in their curriculum as black identity construction. Was made various incursions in curriculum concepts, understanding that is not a closed trial and is a disputed territory (ARROYO, 2011). Silva (2010) indicates that the curriculum theories collaborate to perceive the formation of the subject is on his plurality, subjectivity and identity. Hall (2006) states that identity is influenced by modernity, by the human sciences, presenting non-fixed neighborhoods that can be forged by historical and symbolic processes crossed by the relations of power and knowledge, affecting the curricular practices of teachers. Thus, we understand curricular practices as a set of actions and experiences that bring together teachers, students, employees and the community, among others (AMORIM, 2011). We have the theory of Michel Foucault and Cultural Studies as methodological contributions in the dialogue on power relations and knowledge that challenge the curriculum in a poststructuralist observance and his influence in the school space given its historicity and afrodescendant culture. This study is qualitative, with a bibliographical and documentary approach in questionnaires and semi-open interviews, with the National Curricular Guidelines for Quilombola School Education, the Institution's Political-Pedagogical Project, as well as observing two teachers between 2015 and 2016. The information indicates that, although they don‟t have the knowledge about the Curriculum Guidelines for Quilombola Schooling, the school is concerned with having in her action plan questions that address the black and quilombola‟s identity of the county. Regarding the observations, the first teacher makes use of themes related to black awareness, ancestry and local history in her curricular practices, mostly through literature and poems, connecting the curricular knowledge with the experience of the students in the quilombola‟s community. Already the other teacher, addresses on specific dates, avoiding issues such as racism and others that may point opposition in the opinions of students. Besides, we perceive the silencing of some of the contents of the afro-brazilian culture, understanding that the cultural capital of the teachers select the knowledge transmitted in their classes, as well as exclude others, making epistemicide part of their curricular practices. Concerning the insertion of Mestre Zumba in his classes or until the knowledge of his works, both mentioned not knowing the artist and his works, leading us to problematize his absence in his curricular practices, since the relations of power in the curriculum and the cultural capital of these teachers infer about the institutionalized knowledge and its curricular practices, reproducing absences and silencing on some questions of afro-brazilian and afro-alagoana‟s culture, since their contents are selected, perpetrating in a distance or ignorance of the history of the place itself and, consequently, of their identity